A Real-Time RT-PCR Assay for Genotyping of Rotavirus - Mousavi-Nasab, Seyed Dawood (Iran Biomed J, 2020)
BACKGROUND: HRV is the causative agent of severe gastroenteritis in children and responsible for two million hospitalizations and more than a half-million deaths annually. Sequence characteristics of the gene segments encoding the VP7 and VP4 proteins are used for the genotype classification of rotavirus. A wide variety of molecular methods are available, mainly based on reverse transcription PCR for rapid, specific and sensitive genotyping of rotaviruses. This study describes an alternative real-time PCR assay for genotyping of rotavirus. METHODS: The samples of stools studied in this research have been collected from patients referred to Children's Medical Centers, Tehran, Iran. Rotavirus detection and genotyping were performed using the RT-PCR and semi-nested RT-PCR, respectively. Samples were then genotyped with a new real-time PCR. RESULTS: The real-time PCR was able to genotype all positive samples with a mean C(t )of 28.2. Besides, a concordance rate of 100% was detected between real-time PCR and semi-nested RT-PCR. CONCLUSION: In this study, the genotyping of rotavirus with real-time PCR showed that this method can provide several favorable features, including high sensitivity and specificity, and a wide dynamic range for rotavirus genotyping.